Pengaruh Permainan Lempar Tangkap Bola Terhadap Kemampuan Motorik Kasar Anak Usia 4-5 Tahun - Safitri, Mey; Purbayani, Rini; Herniawati, Ani (JOECE: Journal of Early Childhood Education, 2025)
This study aims to determine the effect of throwing and catching ball games on children's gross motor skills. The research method uses quantitative with the type of Pre Experimental Design type One Group Pretest-Posttest Design. The number of samples used was 13 children with saturated sampling technique. The data collection technique used is using a structured observation sheet. Data processing techniques are carried out using SPSS assistance. The results of the study obtained that children's gross motor abilities before treatment were in the undeveloped category (BB) of 46.15% and 53.85% were in the category of starting to develop (MB). After treatment, children's gross motor skills were in the category of developing as expected (BSH) 46.15% and 53, 86% were in the category of developing very well (BSB). The Wilcoxon test results show that the sig value. (2-tailed) <0.05, then Ho is rejected and Ha is accepted. Thus, it can be concluded that the use of ball throwing games has a positive effect on the gross motor development of early childhood at RA Sabilissalam